Task Effectiveness and Human Fulfillment in Organizations: A Review and Development of a Conceptual Contingency Model - Nemiroff, Paul M.; Ford, David L. (Academy of Management Review, 1976)
This review develops a conceptual contingency framework which considers aspects of relationships among task, organization structure, and individual variables, and which addresses issues of human fulfillment in the work setting. It identifies expected interactions, incongruities, and outcomes among aspects of three sets of variables.